BEHAVIOUR ANALYSIS OF BASIC INPUTS PRICES IN IRAN’S LIVESTOCK SUBSECTOR - J. Azizi; M. Kavoosi-Kalashami; M. S. Allahyari (Journal of Animal and Plant Sciences, 2015)
Decision-making for future products based on the current input prices, variability and fluctuations in the price of products in the livestock subdivision, as well as the high cost of support decisions made by the government in this field, causes sensitivity and distortions in the policies for the inputs supply chain and production in this subsection. So, analysing the concept of these fluctuations and measurement of the basic inputs price behaviour is needed for the Iran's livestock subsection. Present study analyse the monthly retail price behaviour pattern of livestock subsector basic inputs, include local and foreign corn, local and foreign soybean meal, local and foreign fish meal and local and foreign barley, during 2004-2012 using national market data sets. Two types of seasonal unit root tests include FH and Taylor was used to investigate price behaviour pattern for mentioned inputs. The results indicated that among the analysed inputs; only the price behavioural patterns of the local and foreign barley have a complete resemblance with each other. In addition, the price behaviours of the local and foreign corn markets are similar. On the other hand, the price behavioural patterns of the local and foreign soybean meal and fish meal markets are different from one another. Based on this, the adoption of measures and presenting of separate policy packages are required to regulate the market of the two groups of local and foreign inputs, soybean and fish meal; as well as supporting the domestic production of these two commodities. Additionally, similar policies regarding the two local and foreign input groups of corn and barley could reduce the cost of supporting policies in the livestock subsection.
Keywords: behavioural patterns; basic inputs; market regulation; supporting national production; livestock